Efektivitas Pelayanan Publik Feeder Wira-Wiri Kota Surabaya - Fairuz Salsabila Khusnannisa; Sri Wibawani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The city of Surabaya is the capital of East Java province which is known as the city of heroes and is the second largest metropolitan city with a dense population after the city of Jakarta. According to data from the official website of the East Java Central Statistics Agency in 2023, the city of Surabaya has a population of approximately 2,893,698 people, with a large population this will result in an increase in the number of private vehicles which will affect comfort in urban areas. In connection with this, the Surabaya city government has provided a program that aims to overcome problems in the transportation sector, namely the provision of public transportation called Feeder Wira-Wiri by bringing the concept of orderly, safe and comfortable driving or transportation behavior. The aim of this research is to measure the effectiveness of the Wira-Wiri Feeder Public Transport Service in the City of Surabaya. This research uses a quantitative approach using simple descriptive analysis techniques. The data collection technique in this research uses a questionnaire technique. The population of this research is people who use wira-wiri feeder services with a sample of 100 respondents. This research produced interesting findings, including: 1) The results of respondents' responses to the twelve effectiveness measurement indicators showed that all indicators still had values ​​that indicated they were quite effective. However, of the twelve effectiveness measurement indicators, the value indicating quite high effectiveness is found in the flexibility of adaptation indicator with a percentage of 23% and in the productivity indicator with a percentage of 16%. 2) The overall results of the respondents' responses showed that the Surabaya City wira-wiri feeder public transport service was said to be effective with a percentage of 53%.